2018
DOI: 10.1101/463851
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibition of the 60S ribosome biogenesis GTPase LSG1 causes endoplasmic reticular disruption and cellular senescence

Abstract: Cellular senescence is triggered by diverse stimuli and is characterized by long‐term growth arrest and secretion of cytokines and chemokines (termed the SASP—senescence‐associated secretory phenotype). Senescence can be organismally beneficial as it can prevent the propagation of damaged or mutated clones and stimulate their clearance by immune cells. However, it has recently become clear that senescence also contributes to the pathophysiology of aging through the accumulation of damaged cells within tissues.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 57 publications
(77 reference statements)
1
6
0
Order By: Relevance
“…In particular it has been reported that free fatty acids and cholesterol levels can be increased in senescent cells (12,(20)(21)(22)(23)(24)(25) and that ceramides or prostaglandins regulate the onset of senescence 24,59 . In line with our findings, a recent article reported an upregulation of the expression of cholesterol synthesis genes in a model of oncogene-induced senescence 60 . Noteworthy, knockdown of some cholesterol synthesis genes partially bypassed cell proliferation arrest in this system.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In particular it has been reported that free fatty acids and cholesterol levels can be increased in senescent cells (12,(20)(21)(22)(23)(24)(25) and that ceramides or prostaglandins regulate the onset of senescence 24,59 . In line with our findings, a recent article reported an upregulation of the expression of cholesterol synthesis genes in a model of oncogene-induced senescence 60 . Noteworthy, knockdown of some cholesterol synthesis genes partially bypassed cell proliferation arrest in this system.…”
Section: Discussionsupporting
confidence: 93%
“…Noteworthy, knockdown of some cholesterol synthesis genes partially bypassed cell proliferation arrest in this system. However, the mechanisms behind these observations were not deciphered 61 . Our results underline the importance of cholesterol biosynthetic branch downstream of the MVA pathway in the regulation of cellular senescence and allow us to propose a mechanistic model through ERRα activation.…”
Section: Discussionmentioning
confidence: 99%
“…Opiorphin, a 5 amino acid peptide derived from the N-terminus of OPRPN, has many proposed functions including inhibition of aminopeptidase N and MME (neprilysin); however, its role in viral infection is currently uncharacterized. LSG1, a GTPase involved in the biogenesis of the 60S ribosome ( 64 ) has not been studied in the context of viral infections. TCF25, a transcription factor, is also a poorly characterized component of the ribosome-associated quality control pathway that mediates K-48 linkage of ubiquitin to the nascent chain of stalled ribosomal complexes ( 65 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cellular functions of RPL10 are poorly understood (24), but ribosomes and ribosome biogenesis are critical for lipid homeostasis (25). Indeed, inhibition of ribosome biogenesis causes endoplasmic reticular (ER) stress (26), which activates the unfolded protein responses (UPR) and stimulates lipogenesis (27,28). Our lab and others have shown sterol and oxysterol lipids bind to SMO and activate the HH transcriptional program (29,30).…”
Section: Main Textmentioning
confidence: 99%